PRINT MEDIA ECONOMIC-POLITICAL IDEOLOGY IN PREACHING FOREST AND LAND FIRES IN SOUTH OF SUMATERA 2016 - Alfani, Hendra (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Print media coverage of land and forest fire control (karhutla) in the Daily Sumatera Ekspres, Sriwijaya Post and Koran Sindo discuss the reality that has been constructed in accordance with their interests. The three newspapers have their own news composition in discussing and constructing the reality of the forest fire control policy in South Sumatra. The difference arises in relation to business interests and political interests, these two interests are unable to avoid the three newspapers from partiality. The era of media capitalism makes mass media products, including news become commodities. This means that the discourse produced by the media is no longer focused on the interests of the audience as consumers, but discourse is directed at attracting market attention and obtaining economic benefits. Media idealism is increasingly eroded by the influence of the penetration of the ideology of capitalism. The ideology displayed by the mass media has an important influence in building views for certain goals to be achieved in its reporting.